Pocahontas - Ingoglia, Gina (Disney Press, 1995)
The story of Pocahontas, young daughter of Chief Powhatan, has captured the imaginations of children and adults ever since she performed her compassionate and brave acts over 400 years ago.
Keywords: Juvenile Fiction; Native American; People & Places; United States